Effect of Spindle Speed on the Bending Test of Al-1100 in Fraction Stir Welding Joints - Bintoro, Suryanto Agung; Nasution, Arya Rudi; ., Affandi; Siregar, Rahmat Fauzi; Harahap, Jagodang (Rekayasa Material, Manufaktur dan Energi, 2025)
Currently, in the industrial world, many products or components are required to have strong but light properties. Therefore, aluminum material is increasingly being chosen as the main material in the industrial production process. Aluminum and its alloys are classified as light metals that have high strength, corrosion resistance, fairly good electrical conductivity, and are lighter than iron or steel. However, aluminum has a weakness in its welding ability which is not good when compared to other metals. This problem can be overcome by the Solid-State Welding (SSW) welding method. SSW itself is a welding process carried out when the metal is still solid, meaning that the metal does not melt. One of the SSW methods that is often used is Friction Stir Welding (FSW), which is a solid-state welding technology that is very suitable for joining materials such as aluminum. FSW does not require additional materials, but instead utilizes the heat from friction between the probe and shoulder of the welding tool with the surface of the workpiece. This research on Friction Stir Welding aims to determine the effect of variations in feed rate on the strength of 1100 aluminum joints through tensile tests. The pin tool used is made of carbide, cylindrical in shape with a length of 100 mm and a diameter of 3 mm. The test specimen used was aluminum 1100 with a thickness of 3 mm, a length of 200 mm, and a width of 20 mm, and was made into 9 samples. The FSW welding process and the manufacture of test specimens were carried out according to the ASTM E8 standard. During the welding process, the pin tool rotated at 2200 Rpm, and the feedrates used were 50 mm/min, 100 mm/min, and 150 mm/min. After welding, a tensile test was carried out on the FSW joint results. There were nine tensile tests, with each feedrate parameter tested on three samples. The average tensile strength of the FSW joint on a 2200 Rpm spindle with a feedrate of 50 mm/min was 12.34 MPa, at a feedrate of 100 mm/min was 21.53 MPa, and at a feedrate of 150 mm/min was 29.21 MPa.